Abrogation of Notch Signaling in Embryonic TECs Impacts Postnatal mTEC Homeostasis and Thymic Involution - García-León, María Jesús; Mosquera, Marta; Cela, Carmela; Alcain, Juan; Zuklys, Saulius; Holländer, Georg; Toribio, María L. (Frontiers in Immunology, 2022)
Notch signaling is crucial for fate specification and maturation of thymus-seeding progenitors along the T-cell lineage. Recent studies have extended the role of Notch signaling to thymic epithelial cells (TECs), showing that Notch regulates TEC progenitor maintenance and emergence of medullary TECs (mTECs) in fetal thymopoiesis. Based on immunohistochemistry studies of spatiotemporal regulation of Notch activation in the postnatal thymus, we show that in vivo Notch activation is not confined to fetal TECs. Rather, Notch signaling, likely mediated through the Notch1 receptor, is induced in postnatal cortical and medullary TECs, and increases significantly with age in the latter, in both humans and mice, suggesting a conserved role for Notch signaling in mTEC homeostasis during thymus aging. To investigate the functional impact of Notch activation in postnatal TEC biology, we used a mouse model in which RPBJκ, the transcriptional effector of canonical Notch signaling, is deleted in epithelial cells, including TECs, under the control of the transcription factor Foxn1. Immunohistochemistry and flow cytometry analyses revealed no significant differences in TEC composition in mutant (RPBJκ-KOTEC) and wild-type (WT) littermate mice at early postnatal ages. However, a significant reduction of the medullary region was observed in mutant compared to WT older thymi, which was accompanied by an accelerated decrease of postnatal mTEC numbers. Also, we found that organization and integrity of the postnatal thymic medulla critically depends on activation of the canonical Notch signaling pathway, as abrogation of Notch signaling in TECs led to the disruption of the medullary thymic microenvironment and to an accelerated thymus atrophy. These features paralleled a significant increase in the proportion of intrathymic non-T lineage cells, mostly B cells, and a slight decrease of DP thymocyte numbers compatible with a compromised thymic function in mutant mice. Therefore, impaired Notch signaling induced in embryonic development impacts postnatal TECs and leads to an accelerated mTEC degeneration and a premature thymus involution. Collectively, our data have uncovered a new role for Notch1 signaling in the control of adult mTEC homeostasis, and point toward Notch signaling manipulation as a novel strategy for thymus regeneration and functional recovery from immunosenescence.